1994
DOI: 10.1083/jcb.124.3.273
|View full text |Cite
|
Sign up to set email alerts
|

A phosphatidylinositol transfer protein controls the phosphatidylcholine content of yeast Golgi membranes

Abstract: Abstract. SEC14p is required for protein transport from the yeast Golgi complex. We describe a quantitative analysis of yeast bulk membrane and Golgi membrane phospholipid composition under conditions where Golgi secretory function has been uncoupled from its usual SEC14p requirement. The data demonstrate that SEC14p specifically functions to maintain a reduced phosphatidylcholine content in Golgi membranes and indicate that overproduction of SEC14p markedly reduces the apparent rate of phosphatidylcholine bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
156
3

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(170 citation statements)
references
References 34 publications
11
156
3
Order By: Relevance
“…However, we have found that PS-deficient yeast (cho1) produces these vesicles normally and transports proteins by means of the secretory pathway with WT kinetics. This PS-independence of protein transport is remarkable, considering that PS comprises Ï·20% of the yeast Golgi complex membrane (33). Moreover, Drs2p is still required for the formation of exocytic vesicles in the absence of PS, indicating that compensatory changes in cho1 phospholipid composition do not bypass the requirement for Drs2p in protein transport.…”
Section: Discussionmentioning
confidence: 84%
“…However, we have found that PS-deficient yeast (cho1) produces these vesicles normally and transports proteins by means of the secretory pathway with WT kinetics. This PS-independence of protein transport is remarkable, considering that PS comprises Ï·20% of the yeast Golgi complex membrane (33). Moreover, Drs2p is still required for the formation of exocytic vesicles in the absence of PS, indicating that compensatory changes in cho1 phospholipid composition do not bypass the requirement for Drs2p in protein transport.…”
Section: Discussionmentioning
confidence: 84%
“…PLD activity might support 'bypass Sec14p' because it reduces PtdCho levels in Golgi membranes (3). Alternatively, PLD might generate a lipid precursor that is limiting in the Golgi membranes of Sec14p-deficient cells (4,7,9). We wished to address which effect defined the relevant contribution of PLD to 'bypass Sec14p'.…”
Section: Resultsmentioning
confidence: 99%
“…The case for how Sec14p stimulates Golgi secretory function is derived primarily from analyses of mutations that permit efficient Golgi secretory activity (and cell viability) in the face of sec14 deletion mutations (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Characterization of these 'bypass Sec14p' mutations suggests that Sec14p maintains the integrity of a critical Golgi diacylglycerol (DAG) pool that is somehow required for Golgi secretory function (4,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At this point it is still questionable whether these proteins actually transfer these phospholipids between membranes within cells or whether they interact directly with enzymes like PI 4-kinases and PI-specific phospholipase A 2 thereby providing these enzymes with substrates Snoek et al, 1999). In analogy with observations in yeast it has also been proposed that by binding either PI, PC or SPM, PI-TPs act as regulators of phospholipid metabolism at distinct sites in the cell thereby fulfilling the roles of biosensors (McGee et al, 1994;Bankaitis, 2002). Although much remains to be elucidated about their physiological role an observation to be accounted for is that PI-TPa localizes predominantly to the nucleus and cytoplasm whilst PI-TPb is mainly associated with the Golgi complex (De Vries et al, 1995, 1996.…”
Section: Introductionmentioning
confidence: 99%